(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article delves into the captivating realm of Ernest Hemingway’s literary works, specifically focusing on the exploration of character motivations and the anguish they experience. Hemingway, renowned for his ability to depict profound emotions and internal conflicts, presents a rich tapestry of characters grappling with diverse forms of motivation and inner turmoil. Through an analysis of notable works such as "The Old Man and the Sea" and "A Farewell to Arms," this article examines the intricate interplay between motivation and anguish in Hemingway’s characters, shedding light on their complexities and resonating themes.